Analisis Literasi Tujuan Pembangunan Berkelanjutan (SDGs) dalam Membentuk Perilaku Kepedulian Lingkungan - Eko Sutrisno; Nuril Ahmad; Anita Anita; Moch. Ichdah Asyarin Hayau Lailin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The integration of Sustainable Development Goals (SDGs) literacy into higher education serves as a critical instrument for accelerating green campus culture as a manifestation of ecological responsibility. This study examines how systematic implementation of environmental policies and sustainability-oriented curricula transforms theoretical knowledge into tangible, pro-environmental academic behaviors among students. Empirically, the research demonstrates that high student engagement in waste management and energy efficiency reflects the successful internalization of sustainability literacy into daily habituation. Furthermore, the synthesis of ethical values and global sustainability principles empowers students to develop innovative solutions to environmental challenges. As a living laboratory, universities play a pivotal role in bridging the gap between ecological awareness and actionable commitment. The findings indicate that reflective and applied educational approaches significantly enhance students' long-term dedication to environmental preservation, effectively preparing graduates to act as agents of change in professional and societal domains.